Cultural impacts on e-learning systems' success - Aparicio, M. (2016)
E-learning systems are enablers in the learning process, strengthening their importance as part of the educational strategy. Understanding the determinants of e-learning success is crucial for defining instructional strategies. Several authors have studied e-learning implementation and adoption, and various studies have addressed e-learning success from different perspectives. However, none of these studies have verified whether students' cultural characteristics, such as individualism versus collectivism (individualism/collectivism), play a determinant role in the perceived e-learning success. This study provides a deeper understanding of the impact of students' cultural characteristics, for individualism/collectivism, on the perceived outcomes of e-learning systems use. This study proposes an e-learning systems success model that includes a cultural construct, individualism/collectivism. This paper reports an empirical study developed through an electronic survey distributed to higher education students belonging to various learning levels and from various universities. The study applies quantitative methods to obtain results. Our findings demonstrate that learners' perceived individual impact is positively influenced by their satisfaction and e-learning systems' use. Results demonstrate the determinant role of individualism/collectivism on individual and organizational impacts. Students influenced by collective culture perceive more individual and organizational impacts than individualistic culture students. Individualism/collectivism also moderates the users' perceived satisfaction on individual impact, and from individual impacts to organizational impacts. The result shows that for the students with a stronger individualistic culture, satisfaction plays a central role in the way they assess the individual impacts, and individual impacts on organizational impacts. This empirical research discusses the theoretical and practical implications.